2018
DOI: 10.1088/1361-6668/aae7b5
|View full text |Cite
|
Sign up to set email alerts
|

AC losses of Rutherford MgB2 cables made by powder-in-tube and internal magnesium diffusion processes

Abstract: Magnetization losses of Rutherford MgB 2 cables of different sheath materials (Cu, CuNi and Al+Al 2 O 3 ) made by powder-in-tube and internal magnesium diffusion processes were studied experimentally. Short cable samples consisting of 12 strands were measured in the temperature range from 18 K up to 40 K, external fields up to 70 mT and frequencies 72 Hz and 144 Hz. The effects of inter-strand resistance by soldering and external field orientation (perpendicular and parallel) were also tested. The impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In the experiments, all voltages are always measured using the same polarity, left-right, in such a way that in the normal state all measured voltages are positive. AC losses in Rutherford MgB2 cable with and without Al2O3 insulating layer were measured by the system based on the calibration free method [20]. External magnetic field was oriented perpendicular to the plane of cable sample.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the experiments, all voltages are always measured using the same polarity, left-right, in such a way that in the normal state all measured voltages are positive. AC losses in Rutherford MgB2 cable with and without Al2O3 insulating layer were measured by the system based on the calibration free method [20]. External magnetic field was oriented perpendicular to the plane of cable sample.…”
Section: Methodsmentioning
confidence: 99%
“…AC losses in Rutherford MgB 2 cable with and without Al 2 O 3 insulating layer were measured by the system based on the calibration free method [13]. External magnetic field was oriented perpendicular to the plane of cable sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another type of six filament IMD made MgB 2 wire with Al-Al 2 O 3 sheath has shown sufficient thermal stabilization and also promising electro-mechanical properties [15]. It was shown that MgB 2 cable stabilized by OFHC copper in AC regime is heated up by large eddy current losses induced in the high conductive Cu [16], see figure 1(a).…”
Section: Introductionmentioning
confidence: 99%